Authoritative parenting style and lifelong music learning intention: The mediating role of perceived determinants - Wenjun Zheng; Yoon Fah Lay; Anne Noor Sri Juwaneeta Binti Jamaludin (Problems Of education In the 21stcentury, 2024)
The study explores the determinants of lifelong music learning intention among university students, focusing on the mediating roles of attitude toward music learning, perceived social support, and perceived music learning feasibility in the relationship between authoritative parenting style and lifelong music learning intention. This study used structural equation modelling to analyze 617 university students. The structural equation modelling results indicated that authoritative parenting style, attitudes toward music learning, perceived social support, and perceived music learning feasibility are key factors influencing students’ intentions, collectively explaining 72.0% of the variance in lifelong music learning intentions. An intriguing finding is that the mediation analysis highlights the competitive mediating roles of attitude toward music learning, perceived social support, and perceived music learning feasibility between authoritative parenting style and lifelong music learning intention. This recommends that educators and parents adopt holistic approaches to education that are consistent with authoritative and targeted interventions that enhance students’ lifelong learning intentions and contribute to sustainable education